2017
DOI: 10.18869/acadpub.jafm.73.238.25638
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Detection of Cavitation Inception

Abstract: Cavitation phenomenon can cause deterioration of the hydraulic performance, damage by pitting, material erosion, structure vibration and noise in fluid machinery, turbo-machinery, ship propellers and in many other applications. Therefore, it is important to detect inception of cavitation phenomenon. An experimental study has been carried out in order to investigate the noise radiated by various cavitating sources to determine the validity of noise measurements for detecting the onset of cavitation. Measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…They only consider the overall sound pressure level obtained through frequency spectra and no detailed analysis of nature of spectra is reported. Hosien and Selim 35 carried out acoustic measurements in the range 31.5 Hz to 31.5 kHz using a one-third octave band analyzer. After analyzing the sound pressure at various frequency bands, they observed that there was a clear and marked increase in pressure level at 4 kHz at the time of inception.…”
Section: Introductionmentioning
confidence: 99%
“…They only consider the overall sound pressure level obtained through frequency spectra and no detailed analysis of nature of spectra is reported. Hosien and Selim 35 carried out acoustic measurements in the range 31.5 Hz to 31.5 kHz using a one-third octave band analyzer. After analyzing the sound pressure at various frequency bands, they observed that there was a clear and marked increase in pressure level at 4 kHz at the time of inception.…”
Section: Introductionmentioning
confidence: 99%